Optimizing Service Delivery for Customer Satisfaction: Qualitative Study from PT. Bank Syariah Indonesia, Tbk Dumai Branch Office, Indonesia - Lastri, Novelma; Hartutik, Dwi; Musdiana, Andi Desy; Suherman, S. (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study measures customer satisfaction with service at the PT Bank Syariah Indonesia, Tbk, Dumai Branch Office. Service quality and customer satisfaction are two key research indicators. The author employs a qualitative descriptive research approach. The use of qualitative data characterizes qualitative descriptive research. Qualitative descriptive data analysis is frequently used to examine social events, phenomena, or circumstances. The findings of this study show that Bank Syariah Indonesia's Tellers and Customer Service actively assist customers in carrying out services and transactions at the bank. Bank personnel do anything consumers want when they want to open an account, send money, or save money. Islamic banking must demonstrate developments in the growth of its business lines to recognize the issues faced by national Islamic banking, which aspires to increase banking swiftly.